(untitled) (Global Journal of Management and Business Research, 2017)
Human resources are the livelihood of all types of an organization. Even though all types of the organizations are now a days, found to be technology driven, yet human resources are required to run the technology. With all round development in each and every area of the economy, there is stiff competition in the market. With this development and competition, there are lots and lots of avenues and opportunities available in the hands of the human resources. The biggest challenge that organizations are facing today is not only managing these resources but also retaining them. Securing and retaining skilled employees plays an important role in any organization, because employees’ knowledge and skills are central to companies’ ability to be economically competitive. Besides, continuously satisfying the employees is another challenge that the employers are facing today. Keeping into account the importance and sensitivity of the issue of retention to any organization, the present study tries to review the various available literature and research work on employee retention and the factors affecting employee retention and job satisfaction among the employees.